21st Century Competency Analysis of Geography Education Students As an Effort to Support the Implementation of Deep Learning - Pratidina Izza Rahmasyah; Muhammad Al-Farisy; Khoirul Anam (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: 21st century competencies, such as critical thinking, creativity, communication, and collaboration, are the main needs in today's world of education. This study aims to analyze these competencies in Geography Education students and their relationship with readiness to support the implementation of deep learning. Theoretical framework: This study uses an interdisciplinary approach that combines the theories of 21st century skills, constructivist learning, deep learning pedagogy, and geographic education. This approach strengthens the understanding of how essential competencies such as critical thinking, creativity, collaboration, and digital literacy can be developed through meaningful learning processes rooted in constructivist principles. Literature review: The literature review emphasizes the integration of geospatial technologies, project and challenge-based learning approaches, and the role of Deep Learning in fostering conceptual understanding and higher-order thinking skills. Methods: The research method used was a descriptive quantitative approach with the distribution of questionnaires to 100 students. Results: The findings reveal that students' competencies are generally in the high category, with critical thinking (mean score = 4.3) and collaboration (4.21) as the most prominent, while technological literacy remains moderate (3.82). A low standard deviation (0.167) indicates a consistent level of competency across indicators. Implications: The findings highlight the need for strategic curriculum transformation and cross-sector collaboration to develop 21st century competencies through deep learning in geography education. Novelty: The novelty of this study lies in its combined approach of quantitative assessment and critical reflection on the institutional and pedagogical challenges of implementing Deep Learning in higher geography education, offering contextual and actionable strategies for transformative change.